US firms performance during recessions: a comparative case study - Ofori-Bah, Catherine Obiribea (Kansas State University, 2020)
With the majority of economists predicting that the US economy will experience a recession by 2021, it has become increasingly important to explore how well firms do during recessions. Improving understanding of firm characteristics that sustain performance during recessions could provide some learning from the strategies pursued by these firms that maintain their performance during recessions. The study is a case analysis of six US firms, four in the agri-food sector, and two in the technology sector. While numerous performance measures exist, the study intentionally uses return on sales as the performance measure of interest because of its unique characteristic of capturing firms’ current situation over which they have current control. Return on sales, defined as the ratio of net income to sales revenue in the current period, limits performance assessment to current results, allowing for the direct impact of recessions to be measured. The study theorizes that certain firms fare better than others because of their product mix. It also hypothesizes that return on sales as a performance indicator during recessions is determined by how well firms do with their assets and other financial resources. These are tested using 30 years of financial data from Wharton Research Data Services (WRDS), hosted by the Wharton School of Business at the University of Pennsylvania. The six companies investigated were ADM, Bunge, ConAgra and Tyson Foods Inc., IBM and Intel Corporation. The results, estimated using Ordinary Least Squares regression models, showed that the return on sales of Bunge and IBM were unaffected by recessions, while ADM was positively affected by recessions. Meanwhile Tyson Foods, Conagra and Intel were negatively affected by recessions. Additionally, the return on sales is positively affected by the current return on assets for all six firms in the study. The other variables had different impacts on returns on sale.
Keywords: Performance; Recession; Firm characteristics; Agri-food sector